Wild Horse Annie : Velma Johnston and Her Fight to Save the Mustang - Kania, Alan J. (Book collections on Project MUSE., 2012)
In 1950 Velma Johnston, a shy Nevada ranch wife, came upon a horse trailer leaking blood. When she discovered the destination of the trailer and its occupants--a trio of terrified and badly injured wild horses--she launched a crusade that eventually reached the halls of Congress and changed the way westerners regard and treat the bands of mustangs and burros that roam their region.--From publisher description.